2020
DOI: 10.1126/science.abb9601
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of blood testing combined with PET-CT to screen for cancer and guide intervention

Abstract: Cancer treatments are often more successful when the disease is detected early. We evaluated the feasibility and safety of multicancer blood testing coupled with positron emission tomography–computed tomography (PET-CT) imaging to detect cancer in a prospective, interventional study of 10,006 women not previously known to have cancer. Positive blood tests were independently confirmed by a diagnostic PET-CT, which also localized the cancer. Twenty-six cancers were detected by blood testing. Of these, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
401
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(408 citation statements)
references
References 48 publications
(59 reference statements)
6
401
0
1
Order By: Relevance
“…One recent study by Liu et al studied DNA methylation as a further hallmark of a cancer cell, beyond simply mutation [ 64 ]. Another major investigation combined the detection of oncogenic ctDNA mutations, protein markers, and PET-CT (positron emission tomography—computerized tomography) in order to increase the accuracy of cancer detection while specifying the tissue of origin [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study by Liu et al studied DNA methylation as a further hallmark of a cancer cell, beyond simply mutation [ 64 ]. Another major investigation combined the detection of oncogenic ctDNA mutations, protein markers, and PET-CT (positron emission tomography—computerized tomography) in order to increase the accuracy of cancer detection while specifying the tissue of origin [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cancer detection effectiveness of CancerSEEK ranges from 98% for ovarian cancer to only 33% for breast cancer. A feasibility study of CancerSEEK tests has been conducted on a general population of 10,000 women with no history of cancer [ 39 ]. The blood test detected 26 previously unknown cancers of different types with a sensitivity (26/96) of 27.1%, a specificity of 98.9% (9707/9815), and a positive predictive value of 19.4% (26/134) [ 39 ].…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…Among the participants, 27 breast cancers were identified. Among them, only one breast cancer was first detected by the blood test, 20 by standard-of-care screening and six by other imaging means [ 39 ]. Therefore, CancerSEEK tests only have a low sensitivity of 3.7% (1/27) in breast cancer detection.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The DETECT-A study recently demonstrated that assessment of a combination of mutations in cfDNA and protein marker analysis with clinical imaging can safely detect cancer in a previously unaffected, unselected population. 51 The Circulating Cell-Free Genome Atlas Study (CCGA) and STRIVE studies have shown cancer detection and accurate tissue of origin determination using methylation-based approaches (NCT02889978 and NCT03085888). 52 An another recent study, It is important to acknowledge the many questions and challenges that need to be addressed by researchers and healthcare providers;…”
Section: Capp-seq 33mentioning
confidence: 99%